A systematic review of the clinical value and applications of three-dimensional virtual reconstructions in renal tumors - Moldovanu, Claudia-Gabriela; Lebovici, Andrei; Buruian, Mircea Marian (Medicine and Pharmacy Reports, 2021)
Three-dimensional (3D) virtual reconstruction (VR) in the medical sciences has emerged as a novel, exciting and effective tool, with promising results for patients, trainees, and even experienced surgeons. The purpose of this review is to summarize the information on the clinical value and applications of 3D VR in renal tumors published in the last ten years. A literary search of PubMed-MEDLINE databases was performed to identify studies reporting the clinical application and usefulness of 3D VR models in renal tumors. Thirty-seven studies were found to meet the selection criteria and were included in the analysis. Most studies have provided a quantitative assessment focused on the accuracy of 3D VR models in replication of anatomy and renal tumor, on measuring 3D tumor volume and on the clinical value and utility of 3D VR in pre-surgical planning and simulation of renal procedures, with significant reductions of intraoperative complications. Fourteen studies provided a qualitative assessment of the usefulness of 3D VR models, with results showing an improved patient understanding of renal anatomy and pathology, improved undergraduate and postgraduate urology education. Moreover, 3D printing technology is a novel technique, and we are currently in the dynamic era, expanding into new surgical nephron-sparing procedures and the development of printed kidneys for transplantation.